Immuno-biosensor for Detection of CD20-Positive Cells Using Surface Plasmon Resonance - Dariush Shanehbandi; Jafar Majidi; Tohid Kazemi; Behzad Baradaran; Leili Aghebati-Maleki; Farzaneh Fathi; Jafar Ezzati Nazhad Dolatabadi (Tabriz University of Medical Sciences, 2017)
Purpose: Surface plasmon resonance (SPR) sensing confers a real-time assessment of molecular interactions between biomolecules and their ligands. This approach is highly sensitive and reproducible and could be employed to confirm the successful binding of drugs to cell surface targets. The specific affinity of monoclonal antibodies (MAb) for their target antigens is being utilized for development of immuno-sensors and therapeutic agents. CD20 is a surface protein of B lymphocytes which has been widely employed for immuno-targeting of B-cell related disorders. In the present study, binding ability of an anti-CD20 MAb to surface antigens of intact target cells was investigated by SPR technique. Methods: Two distinct strategies were used for immobilization of the anti-CD20 MAb onto gold (Au) chips. MUA (11-mercaptoundecanoic acid) and Staphylococcus aureus protein A (SpA) were the two systems used for this purpose. A suspension of CD20-positive Raji cells was injected in the analyte phase and the resulting interactions were analyzed and compared to those of MOLT-4 cell line as CD20-negative control. Results: Efficient binding of anti-CD20 MAb to the surface antigens of Raji cell line was confirmed by both immobilizing methods, whereas this MAb had not a noticeable affinity to the MOLT-4 cells. Conclusion: According to the outcomes, the investigated MAb had acceptable affinity and specificity to the target antigens on the cell surface and could be utilized for immuno-detection of CD20-positive intact cells by SPR method.